The natural components of mountain Shada and their role in achieving sustainable tourism - Alzahrani, Zahra Ahmed (Journal of Humanities & Social Sciences, 2024)
The study dealt with the natural ingredients in Mount Shada and their role in achieving sustainable tourism, as the study area includes many natural resources that can be used to start a development plan to revitalize the tourism sector in the region, and the researcher put several questions to achieve the research objectives, as the current study aims to identify the natural components in the study area, in addition to knowing the obstacles of tourism in Mount Shada and the most prominent challenges, and in order to achieve the objectives of the study, the researcher used the descriptive and regional approach, and the interview and observation, which is a tool used by the researcher to collect her research data, and the results of the study included confirming the attractiveness of Mount Shada what is characterized by There are many rock formations that appear in the form of hollow-like cavities due to their formation due to the erosion factors experienced by the region, in addition to the presence of ancient drawings and inscriptions in some of the parts of the mountain, which will contribute to the activation of cultural tourism in the study area, and the results of the study also showed that there are some obstacles that cause a decline in tourist traffic, such as the lack of Service and health facilities in the study area, and the study recommended that the natural resources and components in Mount Shada should be local and global development of the sector The tourist is in the study area.